Influencia y evolución de Internet en la Comunicación de la Ciencia y sus fuentes - Dr. Álex FERNÁNDEZ MUERZA (Fonseca, Journal of Communication, 2023)
The Internet is an invention that has revolutionized communications and the history of human civilization. Scientists —broadly speaking— have been the pioneers, creators and early users of the different advances of the Internet and have made it possible for them to later spread to the rest of society. This article shows how the Internet has become a basic tool since its origins for the Communication of Science and its sources, influencing and improving its work